Homeboys: A study of peer-mentoring among African-American males in Chicago in adult education - Warren R. Braden (Adult Education Research Conference, 1993)
The purpose of this paper is to describe the process of peer-mentoring among urban black males and its' effect on their socialization and educational patterns.